2022
DOI: 10.1021/acssynbio.2c00385
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Gene Expression in Clostridium phytofermentans Using Synthetic Promoters and CRISPRi

Abstract: Control of gene expression is fundamental to cell engineering. Here we demonstrate a set of approaches to tune gene expression in Clostridia using the model Clostridium phytofermentans. Initially, we develop a simple benchtop electroporation method that we use to identify a set of replicating plasmids and resistance markers that can be cotransformed into C. phytofermentans. We define a series of promoters spanning a >100-fold expression range by testing a promoter library driving the expression of a luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…Early studies found that conjugative transposons bearing antibiotic resistance genes transfer DNA between Lachnospiraceae ( Barbosa et al, 1999 ). Experimental methods have been developed to transfer plasmid DNA into species of Lachnoclostridium , Roseburia , Eubacterium , Enterocloster , Lacrimispora , and Blautia by conjugation with Escherichia coli ( Tolonen et al, 2009 ; Cuív et al, 2015 ; Sheridan et al, 2019 ; Jin et al, 2022 ) and by electroporation into species of Lachnoclostridium and Butyrivibrio ( Beard et al, 1995 ; Rostain et al, 2022 ) ( Figure 4A ).…”
Section: Cultivation and Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies found that conjugative transposons bearing antibiotic resistance genes transfer DNA between Lachnospiraceae ( Barbosa et al, 1999 ). Experimental methods have been developed to transfer plasmid DNA into species of Lachnoclostridium , Roseburia , Eubacterium , Enterocloster , Lacrimispora , and Blautia by conjugation with Escherichia coli ( Tolonen et al, 2009 ; Cuív et al, 2015 ; Sheridan et al, 2019 ; Jin et al, 2022 ) and by electroporation into species of Lachnoclostridium and Butyrivibrio ( Beard et al, 1995 ; Rostain et al, 2022 ) ( Figure 4A ).…”
Section: Cultivation and Engineeringmentioning
confidence: 99%
“…Native plasmids from Lachnospiraceae have been used as expression vectors ( Hefford et al, 1997 ) and the pMTL plasmid system ( Heap et al, 2009 ) can be applied to identify plasmid origins and resistance markers that function in strains of interest ( Jin et al, 2022 ; Rostain et al, 2022 ). Plasmid origins that have been shown to replicate in Lachnospiraceae include pCB102 from Clostridium butyricum , pBP1 from Clostridium botulinum , pAMβ1 from Enterococcus faecalis , pWV101 from Lactococcus lactis , pIM13 from Bacillus subtilis , and pCD6 from C. difficile , and these plasmids can be maintained using antibiotic resistance genes catP (chloramphenicol), ermB (erythromycin), or aad9 (spectinomycin) ( Sheridan et al, 2019 ; Jin et al, 2022 ; Rostain et al, 2022 ) ( Figure 4B ).…”
Section: Cultivation and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the accurate prediction of RNA folding would be beneficial for investigating off-target effects, and we encourage RNA folding to be considered in computational tools to predict efficient gRNAs ( 25 ). Recently, several dCas12a-based CRISPR interference systems have been developed for tuning gene expression in clostridia ( 13 , 47 , 49 ). In our later work, we would like to investigate the impact of the folding of pre-crRNAs on the efficiency of gene repression.…”
Section: Discussionmentioning
confidence: 99%
“…This nucleasedeficient version of spCas9 binds to target sequences without cutting, effectively blocking gene expression [72]. Tested in various Clostridium species [73,74], CRISPRi offers adjustable gene downregulation, making it a valuable tool for the partial repression of essential genes [75], and the concurrent repression of multiple genes [76]. CRISPRa, on the other hand, involves a nuclease-deficient Cas protein fused with an activation domain for gene upregulation [77].…”
Section: Gene Repression Activation and Editingmentioning
confidence: 99%